Fabrication and characterization of Yb : YAG transparent ceramics - Chua, Kenet Wee Kang (2018)
Transparent polycrystalline ceramics are gaining popularity over their single crystal counterparts in laser ceramics. The popularity is due to the lower manufacturing costs, high manufacturing yield and flexibility to be doped with different types of rare-earth elements to achieve different microstructural properties and high optical transmittance. To study the effects of dopant concentration on morphological properties and optical transmittance, yttrium aluminum garnet doped with 1 at%, 3 at%, 5 at%, 10 at% ytterbium was fabricated using solid state reaction, dry pressing to obtain a green body and vacuum sintering. Samples were polished and characterized using UV-vis spectrophotometry, scanning electron microscopy (SEM) and X-ray diffraction spectroscopy (XRD).Results obtained from the characterization methods were analysed and compared with studies that were previously done. From the SEM images, the samples show an almost pore-free microstructure. It can also be observed that the average grain size of the samples decreases with increasing doping concentration, creating more grain boundaries which serve as light scattering sources. The spectrophotometry results have confirmed that increasing doping concentration increases the amount of grain boundaries, leading to lesser optical transmittance. XRD patterns have confirmed that the samples have pure garnet phase. Analysing the results, it can be concluded that the optimum doping concentration is 1 at% ytterbium to produce sample with high optical transmittance and it is vital to have an almost pore-free micro-structure to produce a high-quality laser ceramic.